Enzymatic Bioremediation of Polyethylene Terephthalate Contaminated Environment - Omachonu Alkali Odoma; Stephen Dio Titus; Silas Verwiyeh Tatah; Chukwuma Stephen Ezeonu (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Enzyme-based bioremediation has emerged as a sustainable and eco-friendly approach to mitigating environmental pollution caused by plastic wastes, pesticides, heavy metals, and industrial effluents. This article explores recent advancements in enzymatic degradation, using polyethylene terephthalate hydrolase (PETases) and mono(2-hydroxyethyl) terephthalate hydrolase (MHETases) for polyethylene terephthalate (PET) breakdown, enzymatic mechanisms for bioleaching. PET is one of the most widely used synthetic plastics, contributing significantly to global plastic pollution due to its persistence in the environment. Conventional methods of PET disposal, such as incineration and landfilling, have proven to be inefficient and hazardous to the environment. In contrast, enzymatic biodegradation offers a promising eco-friendly solution to tackle PET biodegradation through the use of specialized enzymes like PETase and MHETase. We explore the mechanisms of PET biodegradation with focus on key enzymes and their catalytic pathways. Furthermore, the discovery, structure, and activity of PETase, the role of MHETase in processing degradation intermediates, and the contributions of corroborating enzymes such as cutinases, lipases, and esterases were also examined. Despite the promising potential of enzymatic PET degradation, several challenges remain, including enzyme, inefficiency in product recovery, and biosafety concerns associated with genetically modified organisms. In the same vein, regulatory hurdles and the need for standardization in bioremediation practices are discussed. Future research should focus on; the integration of enzymatic biodegradation into the circular bioeconomy, the use of artificial intelligence in enzyme design and the importance of global collaborations in advancing bioremediation strategies.